IMF Staff papers : Volume 29 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1982)
This paper deals with the role of inflationary expectations from a theoretical and empirical point of view. Assume that an economy is growing at a steady pace and that the price level is not expected to change. For many individuals, the direct substitution of consumption goods for money becomes far more attractive than the substitution of financial assets for money. The coefficients for the lagged dependent variable are somewhat higher when the equations contain the interest rate than when they do not. The influences on the demand for money in the United States have not been very different from those in other countries, including the developing countries. This conclusion vitiates the rule of thumb, attributed to Modigliani and supported by Dornbusch and Fischer in their macroeconomic textbook, on how to decide whether the nominal interest rate or the expected rate of inflation should be included as determining the demand for money.